URGNT AND ESSENTIAL: Music in Times of Crisis - Marczyk, Mark (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Mark Marczyk describes the creation of the URGNT livestream series to broadcast from empty Toronto music venues in the early days of the pandemic.